Which Test to Perform for Cystic hydatic Diagnosis and When? - Arab-Mazar, Zahra; Rahmati Roodsari, Sara (Novelty in Biomedicine, 2020)
Echinococcosis is one of the 17 neglected tropical diseases (NTDs) recognized by the World Health Organization. The two major species of medical importance are Echinococcus granulosus and Echinococcus multilocularis (1). There are many studies about diagnostic method of hydatidosis, but there is still the question that which test to perform and when.